A Neonate Diagnosed with Megalencephaly-Capillary Malformation-Polymicrogyria Syndrome with Mutation - Young Mi Park; Yoon-Myung Kim; Seong Hee Oh; Hyun-Seung Jin (Korean Society of Neonatology, 2023)
Megalencephaly-capillary malformation-polymicrogyria syndrome (MCAP) is a rare genetic disorder characterized by megalencephaly, polymicrogyria, body overgrowth, and cutaneous capillary malformations. It has been reported recently that MCAP is related to a somatic mosaic mutation in the phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA) gene. We report a case of hemimegalencephaly with polymicrogyria and cutaneous capillary malformations diagnosed by genetic evaluation of MCAP in the neonatal period. The PIK3CA mutation [c.1635G>T (p. Glu545Asp)] was determined by Sanger sequencing. The patient was treated with a ventriculoperitoneal shunt for progressive hydrocephalus. Because of the dynamic, progressive clinical manifestations and tumor-prone traits of MCAP, early diagnosis is important. Moreover, since the phosphoinositide 3-kinase (PI3K)-specific inhibitor, a targeted therapy for the PI3K/AKT/mTOR signaling pathway is emerging as a new therapy, early genetic diagnosis is becoming increasingly important.